Trends in Subjective Quality of Life Among Patients With First Episode Psychosis—A 1 Year Longitudinal Study - Tan, Xiao Wei; Shahwan, Shazana; Satghare, Pratika; Chua, Boon Yiang; Verma, Swapna; Tang, Charmaine; Chong, Siow Ann; Subramaniam, Mythily (Frontiers in Psychiatry, 2019)
Quality of life (QoL) is often used as an outcome assessment in programs treating patients with first-episode psychosis (FEP). The aim of this study was to examine the longitudinal trend of subjective QoL among patients with FEP and identify the potential influence of patients' social-demographic/lifestyle factors on the trend of QoL. Two hundred and eighty subjects participated in the study. Patient's demographics and subjective QoL were collected at baseline, 6 months and 1 year follow-up. Data were analyzed with a fixed-effect general linear regression model. Subjective QoL demonstrated significant trends of improvement in all four subdomains (physical health, psychological health, social relationships, and environment). Compared with unemployed participants, employed participants were significantly associated with better social relationships (p = 0.005) and environment (p = 0.029) after adjusting for age and gender. Moderation analysis demonstrated a significant improvement of physical health, social relationships, and environment for participants with a higher level of educational achievement, but not for participants with a lower level of educational achievement. Our results indicate that patients with FEP experienced significant improvement in subjective QoL over a 1 year period. Being employed was associated with overall better social relationships and environment among patients with FEP and higher educational achievement was associated with improvement of physical health, social relationship, and environment. Hence, educational achievement and employment could be considered for future optimization of early psychosis intervention programs.